2020
DOI: 10.1021/acs.langmuir.0c01160
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Gas Solubility in Nanopores: A Combined Study Using Classical Density Functional Theory and Machine Learning

Abstract: Geometrical confinement has a large impact on gas solubilities in nanoscale pores. This phenomenon is closely associated with heterogeneous catalysis, shale gas extraction, phase separation, etc. Whereas several experimental and theoretical studies have been conducted that provide meaningful insights into the over-solubility and under-solubility of different gases in confined solvents, the microscopic mechanism for regulating the gas solubility remains unclear. Here, we report a hybrid theoretical study for un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Since the surface charge density Q s * changes monotonically with the separation, the oscillation in / Q s * is due to oscillation in the charge accumulation (see Figure c), which is in turn due to the oscillatory charge density profiles for the small separations. Similar oscillations of the solubilities of gas in the uncharged slit pore and the differential capacitance in the like-charged slit pore have been reported.…”
Section: Results and Discussionsupporting
confidence: 77%
“…Since the surface charge density Q s * changes monotonically with the separation, the oscillation in / Q s * is due to oscillation in the charge accumulation (see Figure c), which is in turn due to the oscillatory charge density profiles for the small separations. Similar oscillations of the solubilities of gas in the uncharged slit pore and the differential capacitance in the like-charged slit pore have been reported.…”
Section: Results and Discussionsupporting
confidence: 77%
“…For example, CO 2 might exist in kerogen nanopores in the dissolved form. ,, It is observed that gas solubility in the solvent in nanopores differs from that in bulk due to the strong confinement effect . There have been some studies on the gas solubility in the solvent in nano-scale pores. They concluded that nano-confinements have significant impacts, either enhancing or reducing the gas solubility in the solvent depending on the confinement properties, pore size, as well as configurations of gas and solvent molecules and their size ratio, and so forth. ,,,,, The enhanced and reduced gas solubilities are referred to as “over-solubility” and “under-solubility”, respectively. The detailed review of the above works can be found in our recent work and a recent review paper .…”
Section: Introductionmentioning
confidence: 99%
“…Because the equilibrium partition coefficients for the systems with various pairwise interactions, including the Lennard-Jones and electrostatic interactions, have been widely investigated and are readily accessible, the permeability and selectivity of these systems can then be conveniently computed by the extended model. [68][69][70][71][72] In other words, one does not need to perform time-consuming nonequilibrium molecular dynamic simulation or complicated DDFT computations. Moreover, the extended model gives a more intuitive physical relation between the thermodynamic states of both reservoirs and the permeability than the numerical calculation based on DDFT.…”
Section: Relating Permeability To Equilibrium Partition Coefficientmentioning
confidence: 99%